Selection of bioindicator species of flumioxazin and saflufenacil residues in the soil (Research, Society and Development, 2020)
Herbicides with residual activity have been used as a weed control strategy in the critical period of crop competition. However, it is necessary to monitor the behavior of these substances in the soil, as they can harm subsequent crops. The bioassay is a simple, inexpensive, fast and highly sensitive method for detecting herbicide residues in the soil, even at low concentrations. The objective of this work was to select plant species as bioindicators of the residual activity of the herbicides saflufenacil and flumioxazin in the soil. The species Panicum maximum cv. Tamani, Sorghum bicolor, Crambe abyssinica, Vigna angularis, Cucumis sativus and Beta vulgaris in a factorial combination with six doses of the herbicide flumioxazin (0; 2.5; 5; 10; 25 and 50 g. ha-1) or seven doses of the herbicide saflufenacil (0; 2.5; 5; 10; 25; 50 and 100 g. ha-1), outlined in randomized blocks, with five replications. For the herbicide saflufenacil the most sensitive species were B. vulgaris, C. abyssinica and C. sativus. For the herbicide flumioxazin the most sensitive species were B. vulgaris and C. abyssinica. Considering that the species suitable for bioassays are easy to grow, fast to grow, sensitive in low doses and easy to visualize the symptoms of phytointoxication, beet was the one that best presented these characteristics for both herbicides.